Pediatric glioblastoma cells are sensitive to drugs that inhibit eIF2α dephosphorylation and its phosphomimetic S51D variant - Eytan, Karin; Versano, Ziv; Oren, Roni; Jacob-Hirsch, Jasmine; Leitner, Moshe; Harmelin, Alon; Rechavi, Gideon; Toren, Amos; Paglin, Shoshana; Yalon, Michal (Frontiers in Oncology, 2022)
We found that pediatric glioblastomas (PED-GBM) cell lines from diffuse intrinsic pontine glioma (DIPG) carrying the H3K27M mutation or from diffuse hemispheric glioma expressing the H3G34R mutation are sensitive to the combination of vorinostat (a histone deacetylase inhibitor) and PARP-1 inhibitors. The combined treatment increased the phosphorylation of eIF2α (P-eIF2α) relative to each drug alone and enhanced the decrease in cell survival. To explore the role played by increased P-eIF2α in modulating PED-GBM survival and response to treatments, we employed brain-penetrating inhibitors of P-eIF2α dephosphorylation: salubrinal and raphin-1. These drugs increased P-eIF2α, DNA damage and cell death, similarly affecting the sensitivity of DIPG cells and derived neurospheres to PARP-1 inhibitors. Interestingly, these drugs also decreased the level of eIF2Bε (the catalytic subunit of eIF2B) and increased its phosphorylation, thereby enhancing the effect of increased P-eIF2α. Transient transfection with the S51D phosphomimetic eIF2α variant recapitulated the effect of salubrinal and raphin-1 on PED-GBM survival and sensitivity to PARP-1 inhibitors. Importantly, either salubrinal or raphin-1 dramatically increased the sensitivity of DIPG cells to radiation, the main treatment modality of PED-GBM. Finally, PED-GBM was more sensitive than normal human astrocytes to salubrinal, raphin-1, and the treatment combinations described herein. Our results indicate that combinations of histone deacetylase inhibitors and PARP-1 inhibitors should be evaluated for their toxicity and efficacy in PED-GBM patients, and point to drugs that increase P-eIF2α or modulate its downstream effectors as novel means of treating PED-GBM.